Penulisan Naskah Web Series Manusia dan Cerita Sampai Bertemu Cahaya Menggunakan Teori Positive Character Arc Sebagai Penunjang Dramatik - Iqlimabelle, Salsa Bila; Kartika, Bambang Aris; Zoebazary, Ilham (Universitas Jember, 2025)
The rise of suicide and bullying today is the basis for the creation of a work entitled Humans and Stories Until Light Meets. This work is a web series script that discusses the relationship between the role of parents in children's lives and children's mental health. This script tells about a child's journey in achieving true happiness or can be referred to as the maturation process. This script uses the positive character arc theory assisted by save the cat technique in its preparation. The purpose of making this script is provide information that parenting has a close relationship with children's mental health, suicide, and bullying behavior in children.